The Spanish Banks' Strategy in Latin America - Miguel Sebastián; Carmen Hernansanz (SUERF - The European Money and Finance Forum, 2000)
The expansion of Spanish banks in Latin America is one of the most important elements of bank internationalisation in recent years. Spanish banks now head the ranking of foreign banks in the region. At first glance, it is paradoxical that at a time of notable progress in the process of European integration, there is an intensification of Spanish investment flows to Latin America. Macroeconomic performance, deregulation, pure banking elements and cultural factors explain the decision of Spanish banks to establish themselves in the region. Given that only a few years have passed since the beginning of the expansion in Latin America, and the economic and financial turbulence ex-perienced by the region in the last two years, it is a little early to properly evaluate the success of this expansion. However, preliminary evidence supports the idea that Latin American revenues have to some extent offset the decline in Spanish net interest income caused by the low interest rate environment in Europe. The presence of Spanish banks in Latin American will increase competition and improve risk management and financial stability.
Keywords: 330; Bank internationalisation; Latin America; Spanish Banks; Internationale Bank; Auslandsinvestition; Spanien; Lateinamerika